An efficient method for predicting train-induced vibrations from a tunnel in a poroelastic half-space. (December 2017) - Zhou, Shunhua; He, Chao; Di, Honggui; Guo, Peijun; Zhang, Xiaohui
Abstract: This paper presents an efficient method for the prediction of vibrations induced by underground railways in a poroelastic half-space. The proposed method accounts for both the saturated porous characteristic of the soil and the free surface effect. An analytical tunnel model, which is coupled with a train-track system, is firstly developed to calculate the dynamic response of the tunnel–soil interface in a poroelastic full-space. By assuming that the near field response of the tunnel is not affected by the existence of the free surface, vibrations of the poroelastic half-space is then calculated by the two-and-a-half-dimensional (2.5-D) boundary integral equation for saturated porous media along with the Green's function for a poroelastic half-space. Soil vibrations generated by the quasi-static and dynamic train load are presented. It is found that an increase of the soil permeability leads to a decrease of the soil displacement. A saturated soil model may be more suitable for calculating the train-induced vibration in water-rich region. Isolation effectiveness of a float slab is also investigated. The simulation results show that floating the track slab can moderately induces the ground vibration, but also causes more transmission of vibration under certain conditions.